Guide extension, unmissable tool in the armamentarium of modern interventional cardiology. A comprehensive review. (1st November 2016) - Fabris, Enrico; Kennedy, Mark W.; Di Mario, Carlo; Sinagra, Gianfranco; Roolvink, Vincent; Ottervanger, Jan Paul; van't Hof, Arnoud W.J.; Kedhi, Elvin
Abstract: Due to the aging population undergoing percutaneous coronary intervention (PCI), interventional cardiologists are confronted daily with treatment of lesions with complex anatomy. Despite improvements in stent devices and PCI techniques, these lesions remain a challenge in terms of procedural success. Guide-extensions (GE) are coaxial "mother and child" catheters employed to facilitate device delivery but they can be used in many different complex scenarios. A comprehensive review of the possible applications of GE and of the GuideLiner™ (GL), the most widely used GE device, is missing. We therefore aim to provide a comprehensive review of all the potential applications of the GL and other GE devices, describe its limitations as well as tips and tricks for successful usage of this GE catheter. Highlights: Guide-extension (GE) can be used in many different complex scenarios. A comprehensive review of all the possible applications of these devices is missing. This review highlights all the potential applications and limitations of GE. GE broadened the subset of lesions that can be successfully treated. GE can be considered a vital tool for modern interventional cardiology.